Manajemen Kesiapan Kepala Sekolah Terhadap Implementasi Koding dan AI sebagai Mata Pelajaran di SMP IT Al-Ghazali Palangka Raya - Purnomo, Widiharto; Nugroho, Piter Joko; Huda, Imam Nur; Widodo, Petrus; Siboro, Magdalena; Pebriani, Dian (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
This study aims to describe how well-prepared school principals are in managing the implementation of Artificial Intelligence (AI) and Coding policies at Al-Gazhali IT Junior High School. Using a qualitative approach, data was obtained through interviews with the principal, vice principal for curriculum, and IT teachers. The results show that readiness management is reflected in four main functions. In terms of planning, the school has prepared a strategic plan, infrastructure, and teacher training. In terms of organization, the principal has formed a special team, clearly divided tasks, and established cooperation with external parties. Learning is implemented in stages, prioritizing hands-on practice and project-based learning, with guidance and monitoring from the principal. Meanwhile, in terms of control, routine supervision and evaluation have been carried out, but they are still predominantly manual and do not fully utilize digital technology. In conclusion, the principal's readiness in implementing AI and Coding policies at SMP IT Al-Gazhali has covered four management functions. This study emphasizes the importance of visionary school leadership, infrastructure support, and a collaborative digital school culture to ensure that the implementation of AI and coding truly benefits students.